2022
DOI: 10.1038/s41598-022-06316-2
|View full text |Cite
|
Sign up to set email alerts
|

Communicate hope to motivate the public during the COVID-19 pandemic

Abstract: How should health authorities communicate to motivate the public to comply with health advice during a prolonged health crisis such as a pandemic? During the SARS-CoV-2 pandemic, for example, people have had to comply with successive restrictions as the world faced multiple races between controlling new waves of the virus and the development and implementation of vaccines. Here, we examine how health authorities and governments most effectively motivate the public by focusing on a specific race: between the Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…Accordingly, policy makers should aim at fostering trust in institution and supply easy‐accessible information about the threat of COVID‐19. Furthermore, insights from social psychology imply that a more positive communication approach increases the willingness to comply with public health regulations (Petersen et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, policy makers should aim at fostering trust in institution and supply easy‐accessible information about the threat of COVID‐19. Furthermore, insights from social psychology imply that a more positive communication approach increases the willingness to comply with public health regulations (Petersen et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Going forward, there is a need to make information about COVID-19 widely available, closer to the broader population, and accessible through various platforms including the issuance of fact sheets and follow-up phone calls to the caregivers [32]. This information ought to be actionable, hope-oriented in a visual format [33], and should come from trusted sources which are health institutions [22] unlike social media is saturated with wrong information [32]. Earlier studies have shown that some caregivers accessed contradicting information which has the potential of compromising the care they render as well as exacerbating their anxiety levels [9].…”
Section: Discussionmentioning
confidence: 99%
“…Among the population's reactions that should be monitored and managed during a crisis, fear is a prime concern ( Peitl et al, 2020 ). Government communication plays a major part in controlling fear ( Petersen et al, 2022 ; Reynolds, 2006 ) and crisis messages should, ideally, both alert and reassure people ( Lachlan et al, 2014 ). While a certain degree of manageable fear can induce people to protect themselves and follow the measures established by government, a higher level may turn into panic, becoming dangerous, and increasing harm and damage ( Sandman, 2006 ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%